Uji Toksistas Ekstrak Etanol Daun Asoka (Ixora coccinea L.) dan Fraksi Pelarut Menggunakan Metode Brine Shrimp Lethality Test (Sam Ratulangi University, 2024)
ABSTRACT This study aimed to determine the toxicity of asoka leaves (Ixora coccinea L.) by determining the LC50 value as well as determining the total phenolic, flavonoid and tannin content of the ethanol extract and asoka leaf fraction. The result of the highest total phenolic content, namely ethanol extract, was obtained at 67,197 μg/mL while the lowest, namely the n-hexane fraction, was obtained at 3,717 μg /mL. The result of the highest total flavonoid content, namely the ethanol extract, was obtained at 39,022 μg /mL and the lowest, namely the ethyl acetate fraction, was obtained at 11,57 μg/mL. The result of the highest condensed tannin content was found in the ethanol extract with a value of 603,185 μg/mL while the lowest tannin content was found in the n-hexane fraction 93,556 μg/mL . The result of the LC50 value in the Brine Shrimp Lethality test method toxicity test were successively obtained from the ethanol extract 92,7517 ppm, the n-hexane fraction 71,1237 ppm, the ethyl acetate fraction 331.5041 ppm and the water fraction 272,9965 ppm. so the toxicity test showed that the fraction n-hexane was very toxic. Based on this research, it can be concluded that the ethanol extract and asoka leaf fraction were toxic. Keywords: Ixora coccinea L., phenolics, flavonoids, tannins, toxicity, BSLT. ABSTRAK Penelitian ini bertujuan untuk menentukan toksisitas dari daun asoka (Ixora coccinea L.) dengan menentukan nilai LC50 serta penentuan kandungan total fenolik, flavonoid dan tanin dari ekstrak etanol dan fraksi daun asoka. Hasil kandungan total fenolik tertinggi yaitu ekstrak etanol diperoleh 67,197 μg/mL. Sedangkan yang terendah yaitu fraksi n-heksana diperoleh 3,717 μg/mL. Kandungan total flavonoid tertinggi yaitu pada ekstrak etanol (39,022 μg/mL) dan yang terendah yaitu pada fraksi etil asetat (11,57 μg/mL). Hasil kandungan tanin terkondensasi paling tinggi adalah pada ekstrak etanol (603,185 μg/mL). sementara kandungan tanin terendah terdapat pada fraksi n-heksana 93,556 μg/mL. Hasil nilai LC50 pada uji toksisitas metode Brine Shrimp Lethality test berturut-turut diperoleh ekstrak etanol 92,7517 ppm. fraksi n-heksana 71,1237 ppm. Fraksi etil asetat 331,5041 ppm. dan fraksi air 272,9965 ppm. Pengujian toksisitas menunjukan bahwa fraksi n-heksana bersifat sangat toksik dibandingkan dengan ekstrak dan fraksi lainnya. Berdasarkan penelitian ini, maka dapat disimpulkan bahwa fraksi dan ekstrak etanol daun asoka bersifat toksik. Kata Kunci: Ixora coccinea L., fenolik, flavonoid, tanin, toksisitas, BLST.